2021
DOI: 10.1177/0003134820988813
|View full text |Cite
|
Sign up to set email alerts
|

REBOA Use, Practices, Characteristics, and Implementations Across Various US Trauma Centers

Abstract: Background Hemorrhage accounts for >30% of trauma-related mortalities. Use of resuscitative endovascular balloon occlusion of the aorta (REBOA) for temporary hemostasis in the civilian population remains controversial. We aim to investigate REBOA practices through analysis of surgeon and trauma center characteristics, implementation, patient characteristics, and overall opinions. Methods An anonymous 30-question standardized online survey on REBOA use was administered to active trauma surgeon members of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…10 As a result, randomized controlled trials on swine models have guided understanding of the physiology and benefits of REBOA placement. 11 In controlled swine hemorrhage models, the average proximal mean arterial pressure (MAP) was significantly greater in Zone 1 compared with Zone 3 occlusion (127.9 § 1.3 vs. 53.4 § 1.1 mmHg). 12 In uncontrolled hemorrhage models, there is a brief supraphysiological MAP achieved directly after inflation, which is transient as hemorrhage continues and causes a decrease in blood pressure for the remaining 30 to 60 minutes of inflation.…”
Section: Advantagesmentioning
confidence: 99%
“…10 As a result, randomized controlled trials on swine models have guided understanding of the physiology and benefits of REBOA placement. 11 In controlled swine hemorrhage models, the average proximal mean arterial pressure (MAP) was significantly greater in Zone 1 compared with Zone 3 occlusion (127.9 § 1.3 vs. 53.4 § 1.1 mmHg). 12 In uncontrolled hemorrhage models, there is a brief supraphysiological MAP achieved directly after inflation, which is transient as hemorrhage continues and causes a decrease in blood pressure for the remaining 30 to 60 minutes of inflation.…”
Section: Advantagesmentioning
confidence: 99%
“…An SBP of 80-90 mmHg should be the target if no brain injury is suspected ('permissive hypotension') with restricted volume therapy using isotonic crystalloids until the target blood pressure (BP) is achieved [18]. In some emergency medical systems, prehospital blood transfusion and the application of an endovascular balloon occlusion are available [19].…”
Section: Initial Emergency Department Management Of Major Traumatic B...mentioning
confidence: 99%
“…There are no prior studies on the practice of REBOA at Canadian trauma centres. A recent study of 345 trauma surgeons in the United States found that 49.3% (170/345) had performed REBOA at least once within the past 2 years; 37.7% of respondents had an overall favorable opinion of REBOA, while 12.2% had an unfavorable opinion and 50.2% were undecided [8].…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%